Evaluation of Quality of Life (BREAST-Q) and Scar Quality (POSAS) after Breast Augmentation. Issue 5 (18th May 2022) - Jawanrudi, Pedram; Bender, Richard; Pennig, Dietmar; Taskin, Berivan; Schäller, Sebastian; Al-Malat, Tarek; Mannil, Lijo
Abstract : Background: This study examines the effects of breast augmentation on women who underwent surgery in Germany regarding their quality of life (QOL) and scar quality using patient-reported surveys. The purpose of this study was to determine if there is an increase in women's QOL after surgery compared with preoperative, and to evaluate their postoperative scar quality. Methods: A prospective monocentric study was conducted on 50 women who underwent breast augmentation with nanotextured silicone-filled implants between October 2018 and December 2020. Of these women, 21 (42%) participated in the preoperative survey (BREAST-Q), and 50 (100%) participated in the postoperative survey (BREAST-Q and POSAS). We used the BREAST-Q questionnaire to measure patients' QOL and the Patient and Observer Scar Assessment Scale to determine the scar quality. Results: Psychosocial well-being increased by 34.3 points according to the Q-score, sexual well-being increased by 35.7, and satisfaction with breasts increased by 48.8. Physical well-being decreased by 12 points. The Patient and Observer Scar Assessment Scale mean scores, according to the patient/observer, are 3.8/2.5 for inframammary scars and 4.4/3.1 for periareolar scars. Conclusions: In this study, we discovered that aesthetic breast augmentation with nanotextured silicone-filled breast implants is associated with significantly higher scores for patient satisfaction, which indicates an improvement in women's QOL.